DIGITAL STORY TELLING IN INCREASING MATHEMATICS LEARNING MOTIVATION IN ELEMENTARY SCHOOL STUDENTS - Nindy Amita (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
Mathematics is one of the subjects that many students avoid in class. The notion that mathematics is difficult and uninteresting is often embedded in students' minds so that it affects motivation in learning. Motivation can affect achievement in learning. The digital era has made students begin to lead learning through technology. It is hoped that the existence of technology can make changes in motivation in students. This study aims to determine whether digital story telling has effectiveness in increasing student motivation, especially in learning mathematics. The research subjects were five fifth grade students of a public elementary school at SD X. The subjects were around 9-10 years old. The study used the one group pre-post test experimental technique. The results of this study obtained the results of the Wilcoxon normality test and obtained a value of 0.038 <0.05. There is a significant change in students' learning motivation after being given the treatment is digital story telling. This research can be used as study material for teachers in increasing student motivation in class, especially mathematics.